2013
DOI: 10.1186/1471-2164-14-705
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and characterization of leaf transcriptome for the development of functional molecular markers of the extremophile multipurpose tree species Prosopis alba

Abstract: BackgroundProsopis alba (Fabaceae) is an important native tree adapted to arid and semiarid regions of north-western Argentina which is of great value as multipurpose species. Despite its importance, the genomic resources currently available for the entire Prosopis genus are still limited. Here we describe the development of a leaf transcriptome and the identification of new molecular markers that could support functional genetic studies in natural and domesticated populations of this genus.ResultsNext generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
7
26
1
Order By: Relevance
“…This may be because they all belong to the family Fabaceae and share a high level of genomes sequence similarity. Similar observations have been reported on other transcriptome studies [41,42]. It is thought that KEGG provides a basic platform for systematic analysis of gene function in terms of gene product networks [43].…”
Section: Transcriptome Sequencing De Novo Assembly and Annotation Fsupporting
confidence: 83%
See 1 more Smart Citation
“…This may be because they all belong to the family Fabaceae and share a high level of genomes sequence similarity. Similar observations have been reported on other transcriptome studies [41,42]. It is thought that KEGG provides a basic platform for systematic analysis of gene function in terms of gene product networks [43].…”
Section: Transcriptome Sequencing De Novo Assembly and Annotation Fsupporting
confidence: 83%
“…Therefore, the development of a known polymorphic SSR marker database for D. odorifera is of great use for diversity studies and breeding programs, as well as being transferable to closely Dalbergia species. In the present study, we identified 35,774 putative SSRs from the transcriptome dataset, which is of great differences in numbers, dominant repeats, and motif types reported from other legume species using Illumina sequencing [41,42,44]. This may be attributable to inconsistencies in genome structure or composition, dataset size, search method, or criteria.…”
Section: Ssr Prediction Validation and Applicationmentioning
confidence: 94%
“…This chloroplast marker presented a specific allele pattern for the Choapa valley that did not reveal population structure, which is consistent with the weak structure detected by the nuclear SSR markers. To our knowledge, the eight chloroplast SSR markers tested in this work had not been used previously to characterize P. chilensis populations, although other chloroplast SSR markers from P. alba had been previously described (Torales et al 2013). As chloroplast DNA is mainly maternally inherited, information from chloroplast microsatellites differs from that obtained from nuclear SSR because cytoplasmic genomes are inherited uniparentally in most angiosperms (Birky 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The quality of the obtained DNA was evaluated on 0.8% agarose gels stained with ethidium bromide and DNA concentration was measured with a NanoDrop ND-1000 spectrophotometer (NanoDrop Technologies, Inc. Wilmington, DE, USA), according to the user's manual. (Mottura et al 2005, Bessega et al 2013, Torales et al 2013, Alves et al 2014, Pomponio et al 2015. This study was based on six nuclear microsatellite loci: Mo05, Mo07, Mo08, Mo09, Mo13, and Mo16, described for P. chilensis by Mottura et al (2005).…”
Section: Outgroupsmentioning
confidence: 99%
“…Next-generation sequencing technologies have increased the opportunity for molecular marker development in non-model study organisms on an unprecedented scale (Torales et al, 2013). To date, only a few genetic maps have been developed for Pyrus spp (Montanari et al, 2013).…”
Section: Molecular Marker Detectionmentioning
confidence: 99%